A modeling and tooth contact analysis method of parabolic modified face gear. (July 2022) - Mo, Shuai; Song, Wenhao; Song, Yuling; Zhang, Yingxin; Huang, Yunsheng
This study proposed a method of designing and modeling a modified parabolic face gear and analyzed its tooth contact characteristics. First, a parabola curve is introduced into the rack profile according to differential geometry and meshing theory and derived the equations of the generating gear, diamond wheel, worm, and modified face gear. Second, a method for modeling the tooth surface of the modified face gear is proposed. Then, the influence of the modified parameters on the face gear is studied. Moreover, the contact equations of the modified face gear and the cylindrical gear were combined to obtain the contact trace. Meanwhile, a coordinate analysis system with installation errors is established to obtain the contact traces and transmission error curves. Finally, the influence of the installation errors on the transmission error of the modified face gear under different modified parameters is analyzed. The results show that the modified face gear is susceptible to installation errors in the tooth width and tooth thickness direction.